The effect of telecare on the quality of life and psychological well-being of elderly recipients of social care over a 12-month period: the Whole Systems Demonstrator cluster randomised trial. (12th December 2013) - Hirani, Shashivadan Parbat; Beynon, Michelle; Cartwright, Martin; Rixon, Lorna; Doll, Helen; Henderson, Catherine; Bardsley, Martin; Steventon, Adam; Knapp, Martin; Rogers, Anne; Bower, Peter; Sanders, Caroline; et al.
Abstract: Background: home-based telecare (TC) is utilised to manage risks of independent living and provide prompt emergency responses. This study examined the effect of TC on health-related quality of life (HRQoL), anxiety and depressive symptoms over 12 months in patients receiving social care. Design: a study of participant-reported outcomes [the Whole Systems Demonstrator (WSD) Telecare Questionnaire Study; baseline n = 1, 189] was nested in a pragmatic cluster-randomised trial of TC (the WSD Telecare trial), held across three English Local Authorities. General practice (GP) was the unit of randomisation and TC was compared with usual care (UC). Methods: participant-reported outcome measures were collected at baseline, short-term (4 months) and long-term (12 months) follow-up, assessing generic HRQoL, anxiety and depressive symptoms. Primary intention-to-treat analyses tested treatment effectiveness and were conducted using multilevel models to control for GP clustering and covariates for participants who completed questionnaire measures at baseline assessment plus at least one other assessment ( n = 873). Results: analyses found significant differences between TC and UC on Short Form-12 mental component scores ( P < 0.05), with parameter estimates indicating being a member of the TC trial-arm increases mental component scores (UC-adjusted mean = 40.52; TC-adjusted mean = 43.69). Additional significant analyses revealed, time effects on EQ5D (decreasing over time) and depressive symptoms (increasing over time). Conclusions: TC potentially contributes to the amelioration in the decline in users' mental HRQoL over a 12-month period. TC may not transform the lives of its users, but it may afford small relative benefits on some psychological and HRQOL outcomes relative to users who only receive UC. International Standard Randomised Controlled Trial Number Register: ISRCTN 43002091.